Peace of Mind and Organizational Citizenship Behavior - Ariyabuddhiphongs, Vanchai (Archive for the psychology of religion, 2014)
A Thai company organizes a weekly sermon and meditation session for its clients and members. We hypothesized that vipassana meditation’s positive effects in work would be manifested in peace of mind, loving kindness, and organizational citizenship behavior (ocb), that peace of mind would predict ocb, and that loving kindness would mediate the relationship of peace of mind to ocb. Peace of mind is operationally defined as the experience of inner peace and harmony; loving kindness as the thoughts, words, and acts of kindness extended to all creatures; and ocb as individual behavior that involves courtesy, civic virtue, sportsmanship, conscientiousness, and altruism. We conducted a study among 147 vipassana meditation participants; the results supported the hypotheses. Participants’ peace of mind predicted ocb and loving kindness significantly mediated the peace of mind-ocb relationship. The beneficial effects of vipassana meditation suggest its adoption by organizations to foster efficient functioning.